PTU-140 Does a dedicated inflammatory bowel disease (IBD) pharmacist clinic improve patient safety ?. (8th June 2018) - Steel, Alan; Morgan, Helen; Tan, Wei; Marvin, Vanessa; Wahed, Mahmood
Abstract : Introduction: Immunomodulator (IMM) drugs are widely used in the treatment of IBD. These drugs are very effective but also have well recognised, potentially serious, side effects including bone marrow suppression, liver toxicity and pancreatitis. There is a developing role in the UK for pharmacists utilising their specialist knowledge and skills in direct patient facing activities. We aimed to review the impact of the introduction of a specialist IBD pharmacist clinic in the management of IBD patients Methods: IBD patients seen by the IBD pharmacist were identified from our database. Clinical history, demographics, side effects, blood monitoring including TGN levels were recorded. The total number of actual and virtual clinic visits managed by the pharmacist was determined and the outcome of these visits was categorised. The pharmacist responsibilities included initiation of IMM therapy for patients, medication counselling, prescribing, blood tests and follow up appointments allowing assessment of both clinical response and safety monitoring. Results: Between Nov 2015 and Feb 2017, 367 pharmacist out-patient appointments and 83 pharmacist virtual clinic reviews for 176 IBD patients (Crohn's disease 101, ulcerative colitis 69, IBDU 6) were undertaken. Of the 176 IBD patients, 164 (93%) were on thiopurines, 9 (5%) on methotrexate and 3 (2%) on ciclosporin. Patients visits with the IBD pharmacist were for the following reasons: initiation of IMM treatment (including counselling, dose titration, 2 weekly blood monitoring for the first 2 months), 92 appointments (appts); post initiation, 95 appts; routine 3 monthly monitoring, 145 appts; intensive monitoring (e.g. dose escalation), 45 appts; and dose optimisation (combination therapy with allopurinol) 63 appts. 89% of clinic appts were managed independently by the pharmacist. 196 appointments resulted in 230 actions in patient management to be undertaken. These were: side effects assessed and pt reassured (37 actions); symptoms assessed and pt reassured (27); adherence support (15); dosing advice (8); dose increased (low thioguanine nucleotide (TGN)) (27), dose decreased (high TGN, abnormal blood tests) (32); allopurinol combination therapy (11); azathioprine switch to 6MP (5); other medication (12); physician review (15); other (34). As a result of the IBD pharmacist in the clinic, a pharmacy helpline was developed with patients calling or emailing the pharmacist for advice in between clinic visits (122 calls/emails over 37 weeks). Conclusion: The IBD pharmacist has a key role in the management of IBD patients contributing not only to medication monitoring, prescribing, and safety but also allowing greater capacity in the physician's, often highly stretched IBD clinics.